Life Stories in Management Research: An Introductory Guide from the Organizational Role - Mendoza-Woodman, Jorge (2023)
This article provides a guide that focuses on adopting a constructivist approach to analyze organizational management through the use of narrative analysis and life stories. It also highlights the relevance of personal experiences and the organizational role as sources of knowledge, provides a systematic method for data collection through shared narratives and presents various alternatives for rigorous data interpretation. The primary objective is to encourage the generation of new knowledge from the experiences and narratives of those individuals involved in the management of the organization. This significantly enriches the understanding of these phenomena and contributes novel approaches to the field of research.